AISYAH BINTI ABU BAKAR RA : WANITA ISTIMEWA YANG MELAMPAUI ZAMANNYA - Aisyah Tidjani (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2016)
Aisyah binti Abu Bakar Woman figure in Islam which was said passing her era, and known by her intelligence. Her act in Islamic history was so strategic and giving more real contribution to development of Islamic science. It was become references by an intellectual of Muslim and Rasulullah’s friends. Her intelligence was getting the better than other woman in her era, especially in qur’anic interpretation (tafsir), prophetic traditional (hadits), fiqh, medical and literature. She has sensitivity in understanding about some medicines that given to Rasulullah, until she could know well about it. Besides that, Aisyah was the only one girl who was married by Rasulullah.